Development and Application of a High Performance Liquid Chromatography-Triple Quadrupole Mass Spectrometry Method for the Determination of Glycosidic Aroma Precursors in Tea - SU Desen, LIN Xiuxian, ZHENG Yunyun, HUANG Minmin, WANG Rangjian, LIU Guowen, YAO Qinghua (Shipin Kexue, 2025)
The present study proposed a method for the determination of 12 glycosidic aroma precursors (benzyl β-D-glucopyranoside, benzyl β-primeveroside, 2-phenylethyl β-D-glucopyranoside, 2-phenylethyl β-primeveroside, geranyl β-D-glucopyranoside, geranyl β-primeveroside, linalyl β-D-glucopyranoside, linalyl β-primeveroside, nerolidyl β-D-glucopyranoside-1, nerolidyl β-D-glucopyranoside-2, nerolidyl β-primeveroside-1, and nerolidyl β-primeveroside-2) in tea using high performance liquid chromatography-triple quadrupole-mass spectrometry (HPLC-TQ-MS), and applied it to evaluate the compositional characteristics of glycosidic aroma precursors in five types of tea from Fujian province of China. Samples were extracted with methanol, purified by the QuEChERS method, and separated on a ACQUITY UPLC BEH C18 column using a mobile phase composed of water and acetonitrile with 5 mmol/L ammonia as a regulator. The separation was completed within 10 minutes. The limit of detection (LOD) and the limit of quantification (LOQ) of the proposed method ranged from 0.21 to 4.39 ng/mL and from 0.69 to 14.64 ng/mL, respectively, and the average recoveries were in the range of 81.34%-114.72%, with relative standard deviations (RSDs) of 0.40%-8.98%. Partial least squares-discriminant analysis (PLS-DA) was performed to distinguish the differences in glycosidic aroma precursors among Dahongpao tea, Shuixian tea, Tieguanyin tea, Tanyang Gongfu tea, and Baimudan tea. It was found that the compositional characteristics of glycosidic aroma precursors in tea were significantly affected by both tea variety and making process. Benzyl β-primeveroside, 2-phenylethyl β-primeveroside, geranyl β-primeveroside, and geranyl β-primeveroside were the key differential compounds. The conclusion of this study has a positive significance for optimizing the tea-making process and regulating tea quality.